Karakterisasi Panjang Gelombang Tanaman Daun Bebele dan Kangkung yang Tumbuh Di Pulau Lombok Sebagai Dye Sensitized Solar Cell (DSSC) - Listari, Nening; Agustini, Dwi (Hydrogen: Jurnal Kependidikan Kimia, 2019)
Dye Sensitized solar cells (DSSC) can use two types of coloring, namely dyes derived from organic and inorganic materials. The choice of natural dyes is preferred by looking at the enormous potential of biodiversity in Indonesia, where there are still many untapped especially for plants that have a tendency to be colored or contain chromophore dyes such as chlorophyll (play a role in the absorption of light for photosynthesis). The wavelength when characterizing the dye as a solar cell must be in the visible area (400 to 800nm). In this study the natural dyes used are bebele leaves and kangkung which grow on the island of Lombok. The wavelength obtained for fresh bebele is 553nm, 605 nm and 665nm. The wavelength obtained for fresh kangkung leaf is 664.5 nm with the highest absorption peak. From the results of the absorption stated that natural dyes have chlorophyll a and b groups which are absorbed in the UV-Vis region 600nm to 700nm which means that they absorb the red most strongly. In the measurement of current strength and efficiency with multimeters on organic dyes in a row that is fresh bebele leaves5 Î¼A /cm2; 0.156; fresh kangkung leaves 4.2 Î¼A/cm2; 0,131; dried bebele leaves 4 Î¼A/cm2; 0.13; dried kangkung leaf 3 Î¼A /cm2; 0.088.